Current clinical practice status of Korean medicine for managing female infertility: A cross-sectional survey - Choi, Jiae; Lee, Myeong Soo; Ko, Mi Mi; Choi, Tae-Young; Jun, Ji Hee; Lee, Hye Won; Ang, Lin; Jo, Junyoung; You, Sooseong (Complementary therapies in clinical practice, 2020)
This survey aimed to investigate clinicians’ perceptions and current practice patterns of Korean medicine (KM) treatment for female infertility. A questionnaire on clinical practice patterns of KM treatment for female infertility was constructed and distributed to 703 KM doctors (KMDs). A total of 20.5% of physicians (n = 144/703) completed the survey and delivered integrative care for female infertility patients. Integrative care mainly consisted of acupuncture, herbal medicine, and moxibustion. The participants largely relied on radiological findings on ultrasonography and hormone tests for diagnosis. The most frequently prescribed herbal medication was Jogyeongjongok-tang (Tiaojing Zhongyu decoction), and the most frequently applied acupoints were SP6, CV4 and ST36. This study provides expert opinions and information on actual clinical practice patterns of KM for treating female infertility. However, we cannot completely discount the possibility that biased selection of subjects and the low response rate limit the interpretations of the study results. •We surveyed 703 Korean medical (KM) doctors for investigate the clinical practice status of KM for female infertility.•The most frequently used herbal medicine and acupuncture points were Jogyeongjongok-tang , and SP6, CV4 and ST36, respectively.•This study provides expert opinions and information on actual clinical practice patterns of KM for treating female infertility.